AN ANALYSIS OF GENERIC STRUCTURE IN STUDENTS’ EXPLANATION WRITING ABILITY - Elwin Piarawan Zebua (TEHUDE: Jurnal Ilmiah Pendidikan Bahasa Inggris, 2022)
Regularly, students faced problem to follow the procedures of writing explanation text in the concept of generic structure. This research was aimed to describe the generic structure of explanation text written by the eleventh grade students and factors affecting it by taking the descriptive qualitative as the research method. The informant of the research was class XI-OTKP students of SMK Negeri 1 Gunungsitoli Barat which consisted of 25 students. The data were collected through students’ worksheets which analyzed through Seven-Point, Two- Trait Rubric for Explanatory Genre and interview that was analyzed through reading/memoing, describing what is going on in the setting, and classifying research data. The result showed that the generic structure of explanation text written by the eleventh grade students was incompletely fulfilled. After conducting the analysis of students’ answer in interview sheets, the result showed that most of the students were affected by less-knowledge about the generic structure of explanation text, the understanding of the topic of explanation, the learning motivation and the acquisition of English which affected their writing